FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT MEMBELI RUMAH BERSUBSIDI DI KECAMATAN MEDAN MARELAN - Manda Dwipayani Bhastary (Universitas Medan Area, 2016)
Along with the increasingly difficult economic situation and the many demands need to be met by the community then purchase a house in cash more difficult, especially for people who are middle to lower economic level. Thus, the purchase of subsidized home loans among people becomes a very attractive option. Based on data collected by an increase in the demand for subsidized housing, especially in the district of Medan Marelan. It can be seen from the increasing property business. Private developers tend to be more interested in the property business (houses) in the district of Medan Marelan because the area is still beautiful and population growth rates are higher. The high level of competition among developers of property (housing), makes an analysis of the factors that influence the decision of the community in need of subsidized housing memebeli known.This study aimed to analyze and determine whether the factor of location, public revenues, ease of access to credit, and public facilities, the market price of the home as well as legislation affecting people's decision in the purchase of subsidized housing in the district of Medan Marelan.The results showed that the location factor is the most dominant factor of the factors that influence the decision to buy subsidized housing communities in the district of Medan Marelan with a coefficient of determination of 42.1%.Keywords: Purchase Decision Factors